Analysis of Zonal Winds in Determining the Onset of the Season to Support Fishing Activities on the Western Coast of Makassar City - Wardhani, Herbuana Yoga; Asbar, Asbar; Hamsiah, Hamsiah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study examines the determination of the fishing season to support fishermen’s activities on the western coast of Makassar City through the analysis of zonal winds. Wind is a crucial meteorological element, influenced by its direction and speed. Coastal wind patterns differ from those in open seas due to the interaction between land and sea breezes. As Makassar City is located in a coastal area, many of its residents work as fishermen whose activities are significantly influenced by weather conditions. Weather information plays a critical role in ensuring optimal fishing outcomes and improving safety for fishermen before they venture to sea. This research was conducted on the western coast of Makassar City using both quantitative and qualitative methods. Quantitative analysis involved windrose diagrams to identify wind trends and bar charts to analyze rainfall patterns, while qualitative analysis employed questionnaires with 46 respondents. The findings indicate that zonal wind data from the study area cannot reliably determine the fishing season due to the local influence of land-sea wind interactions, which disrupt the monsoonal wind patterns. However, weather conditions were found to have a significant impact on fishing activities, with a Likert scale score of 89.86%, indicating a strong influence. Seasonal weather information enhances fishermenâ€™s safety, guides the selection of fishing gear, and increases catch yields. Therefore, providing reliable seasonal weather information is essential for supporting fishing activities on the western coast of Makassar City.